PERAN KEUNGGULAN BERSAING MEMEDIASI PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN - Hajar, Siti; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 5 No 10 (2016), 2016)
The purpose of this study was to determine the effect of entrepreneurial orientation on performance marketing mediated competitive advantage. Research was conducted on the retail clothing store owner in the form of small-scale outlets (outlet) clothing boutiques. The sample size of 105 respondents, by using non-probability shaped sampling. Teknik incidental and purposive analysis of the data used is Path Analysis and Sobel test. Based on the analysis it was found that the regression model used in compliance with the assumptions of classical test. This study found that 1) Orientation Entrepreneurship positive and significant effect on the Competitive Advantage; 2) Competitive Advantage positive and significant effect on marketing performance; 3) Orientation Entrepreneurship positive and significant effect on marketing performance; 4) Competitive Advantage proved to be positive and significant mediating effect on the Performance Marketing Entrepreneurship Orientation.
Keywords: orientation entrepreneurship, competitive advantage, performance marketing, retail